An Empirical Study of Iran’s Hand Woven Product Market - Shayegan, Soheila (Eastern Mediterranean University - Doğu Akdeniz Üniversitesi, 2020)
The production of carpets has been an economic pillar of Iran for more than four hundred years. In time that the carpet industry was booming because of the reputation and demand for Iranian carpets in worldwide market and also because of the development of the Iranian urban carpet workshops, Europe’s tendency toward this industry revolutionized the organization of production. Albeit, Iranians handwoven has been still keeping its first and foremost position in the global market. Therefore, this work tries to investigate the purchasing intention of Iranian’s handwoven Persian Carpets from customers’ standpoint. In this study, the primary data are under consideration in such a way that questionnaires are structured as a paper questionnaire that respondents complete all alone. When the questionnaire is arranged and structured by shrouded steps in the past segment, it is separated into twelve sections. The first section of the questionnaire guarantees that the correct respondent will continue through the survey. A group of 50 respondents have been chosen aimlessly from the population to pre-test the questionnaire. Finally, 300 respondents from the population had been chosen by chance and were presented the questionnaire to respond. The most generally utilized software for statistical examination is PLS and IBM's SPSS. Totally, 10 hypotheses were developed to be investigated in this study so as to indicate the association between attitudes as functions and consumer's purchasing intention. The result of the analysis and collected information from previous studies are consistent with each other. iv All in all, we found out that attractiveness of a product not only has a positive effect on consumers’ attitude but also the relationship between attractiveness and mediator perceived value is a full mediation. Additionally, the results of our study revealed that both utility and originality play a part as partial mediators between perceived value and attitude toward purchasing Iranian carpets. Keywords: Coolness, Attractiveness, Utility, Originality, Perceived Value, Purchasing Intention, Iranian Carpet.

ÖZ:Halı üretimi dört yüz yıldan uzun bir süredir İran için ekonomik bir sütun olmuştur. Halı endüstrisinin dünya pazarındaki İran halılarına olan itibarı ve talebi ve aynı zamanda İran kentsel halı atölyelerinin gelişmesi nedeniyle patladığı zaman, Avrupa'nın bu endüstriye eğilimi üretim organizasyonunda devrim yarattı. İranlılar el dokuması da olsa küresel pazardaki ilk ve en önemli konumunu koruyor. Bu nedenle, bu çalışma İran'ın el dokuması İran Halılarının satın alma niyetini müşterilerin bakış açısından araştırmaya çalışıyor. Bu çalışmada, birincil veriler, anketlerin katılımcıların tek başına tamamladıkları kağıt anket şeklinde yapılandırıldığı şekilde değerlendirilmektedir. Anketin ilk bölümü ankete doğru katılımcının devam edeceğini garanti eder. Beş puanlık bir öncüye sahip Likert ölçeğinin yapısı seçilir ve referans formları anketi şekillendirmek için birleştirilir. Anketi önceden test etmek için 50 katılımcıdan oluşan bir grup amaçsızca nüfustan seçilmiştir. Son olarak, popülasyondan 300 katılımcı tesadüfen seçilmiştir ve cevap vermek için anket sunulmuştur. İstatistiksel inceleme için en sık kullanılan yazılım PLS ve IBM SPSS'dir. SPSS kullanarak, Pearson ilişki katsayısının iki faktör arasındaki doğrusal ilişki ilişkisinin gücünü ölçtüğü Pearson korelasyon katsayısı testinin yapılması düşünülebilir (Sedwick, 2012). Bu çalışmada, işlev olarak tutumlar ile tüketicinin satın alma niyeti arasındaki ilişkiyi göstermek amacıyla toplam 10 hipotez araştırılmak üzere geliştirilmiştir. Analiz sonuçları ve önceki çalışmalardan toplanan bilgiler birbiriyle tutarlıdır. vi Sonuçta, bir ürünün çekiciliğinin sadece tüketicilerin tutumu üzerinde olumlu bir etkiye sahip olmadığını, aynı zamanda çekiciliğin ve arabulucunun algılanan değeri arasındaki ilişkinin tam bir arabuluculuk olduğunu, bağımsız bir değişken olduğunda arabuluculuğun çağrıldığını bilerek öğrendik. aracı değişken yoluyla bağımlı değişken (ler) üzerindeki etkiler. Ayrıca, çalışmamızın sonuçları, İran halılarının satın alınmasına yönelik algılanan değer ve tutum arasında hem fayda hem de özgünlüğün kısmi aracılar olarak yer aldığını ortaya koymuştur. Bununla birlikte, çekiciliğe kıyasla, algılanan değerin çekiciliğe aracılık ettiği ölçüde fayda ve özgünlükten daha fazla olduğu belirtilmiştir. Anahtar Kelimeler: Serinlik, Çekicilik, Fayda, Özgünlük, Algılanan Değer, Satın Alma Niyeti, İran Halı.
Master of Arts in Marketing Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2020. Supervisor: Assoc. Prof. Dr. Emrah Oney
Keywords: Marketing Management; Carpets-Rugs-Commerce; Coolness; Attractiveness; Utility; Originality; Perceived; Value; Purchasing Intention; Iranian Carpet